Ranah Afektif Perspektif Al- Ghazali (Kajian Terhadap Kitab Kimia Saâ€™adah) - Munif, Muhammad Rifqi (Attractive : Innovative Education Journal, 2020)
This article was motivated by education in Indonesia which was still focused on cognitive domain. It has the big impact on the round life reality. The aim of this study was to determine the affective domain according to â€œBook of Kimia al-Saâ€Ÿadahâ€ and how the relevance of al-Ghazali's perspective on the affective domain education in Indonesia. The researcher used library research. In collecting the data the researcher used the documentation method which consisted of primary and secondary sources. Primary sources, namely â€œBook of Kimia al-Saâ€Ÿadahâ€ and secondary books, namely "Ulumuddin al-Ghazali and the others references. Analytical method used the deductive and inductive method. The result showed that in the book of Kimia al-Saâ€Ÿadah, Al-Ghazali explained that the affective domain of the nature of the heart as a king in the body, the tendency of the heart, the uniqueness of the heart, and how to stabilize the heart itself so as to bring up the person who has morality karimah. Al-Ghazali's thought is relevant to the Pancasila philosophy, because al-Ghazali's approach also uses a philosophical approach that is in accordance with the character of the Indonesian nation. But now moral education that is often taught is only given without guidance. Keywords: Affective Domain, Moral Education, Kimia Saâ€™adah